The complete chloroplast genome sequence of Ficus pandurata Hance var. angustifolia W.C. Cheng (Moraceae) - Xiaoqing Zhang; Fei Xu; Ling Guo (Mitochondrial DNA. Part B. Resources, 2022)
Ficus pandurata var. angustifolia is an edible plant popular throughout China where it has a long history of use in traditional She medicine. Using Illumina sequencing, we assembled and annotated the complete chloroplast (cp) genome of F. pandurata var. angustifolia which is 160,526 bp and encodes 130 genes, comprised of 85 protein-coding genes, 37 transfer RNA (tRNA) genes, and eight ribosomal RNA (rRNA) genes. Phylogenetic analysis resolved F. pandurata var. angustifolia as sister to F. deltoidea which together formed a clade with F. heteromorpha. This complete cp genome sequences is a valuable resource for future studies of evolution and species delimitation in genus Ficus as well as variety breeding and conservation for this species.